AhR-Mediated, Non-Genomic Modulation of IDO1 Function - Pallotta, Maria Teresa; Fallarino, Francesca; Matino, Davide; Macchiarulo, Antonio; Orabona, Ciriana (Frontiers in Immunology, 2014)
The evolutionary process has conferred a dual – enzymic and signaling – function on the ancestral metabolic enzyme indoleamine 2,3-dioxygenase 1 (IDO1), which has long been known for converting the essential amino acid tryptophan into neuroactive and immunoactive catabolites (kynurenines). In addition to tryptophan catabolic activity, phosphorylated immunoreceptor tyrosine-based inhibitory motifs (ITIMs), present in the IDO1 protein, act as docking sites for different molecular partners, which activate positive (transcriptional) or negative (posttranslational) modulation of IDO1 protein. The ligand-operating transcription factor aryl hydrocarbon receptor (AhR) contributes to Ido1 transcription, and it can be operated by both exogenous as well as endogenous ligands, including L-kynurenine itself, the first byproduct of tryptophan catabolism. Ligand-bound AhR is also a component of an ubiquitin ligase complex, responsible for regulatory proteolysis of different target proteins. Because IDO1 half-life is controlled by the ubiquitin-proteasome system, we here discuss the possibility that AhR, in addition to enhancing Ido1 transcription, contributes to IDO1 regulation by a non-genomic mechanism affecting the protein’s half-life.